Influence of crystals distribution on the photoluminescence properties of nanocrystalline silicon thin films - Cerqueira, M.F.
Nanocrystalline silicon thin films doped with erbium were produced by reactive magnetron RF sputtering. Their structural and chemical properties were studied by X-ray diffractometry at grazing incidence, micro-Raman, spectroscopic ellipsometry and Rutherford Backscattering Spectroscopy, respectively. Films with different crystalline fraction and crystallite size were deposited. Since the luminescence efficiency of Er-doped nc-Si films is strongly influenced by the microstructure and impurity content (i.e. H, O, Er), the photoluminescence characteristics are discussed in terms of the microstructure. The novelty of these films, if compared to usually investigated structures with the nanocrystals embedded in SiO2, is their relative high conductivity, which makes them attractive for device applications